Literature Review: The Effect of Nutrition Education on Knowledge, Attitude, and Nutrition Practice on Adolescents in Indonesia - Dewi, Nikmah Utami; Hardinsyah,; Hartini, Diah Ayu; Pradana, Fendi; Bohari, (International Journal of Psychosocial Rehabilitation, 2020)
Nutrition education is a way which has been done mostly to alter nutrition behaviour globally. However, in Indonesia, there is no information yet which describes on success evaluation of nutrition education improves nutrition behaviour such as knowledge, attitude, and practice. The aim of this article is to give review of various evidences of nutrition education in Indonesia in order to improve knowledge, attitude, and behaviour of adolescents. Literature search was conducted by using databases of google scholar and repository of Institut Pertanian Bogor with keywords “Nutrition Education”, “Nutrition Education for Adolescents”, and “Nutrition Education Intervention” by involving the literature published between 2013 and 2019. Total 21 studies show that there is only one study which is unsuccessful to improve the knowledge and attitude, but only four studies (36.4%) that can improve nutrition practice. The factors which affect nutrition education on adolescents in Indonesia are duration and period of intervention, the strategy based on the theory of behavioural change, and involving multi elements such as peer friends and trained facilitators.